(untitled) (Research, Society and Development, 2021)
The study aims to describe the results obtained from pharmacognostic quality parameters, phytochemical prospection and in silico studies of monoterpenes isolated from Dysphania ambrosioides. Leaves and stems were used, which were dried and sprayed, the powders were submitted to pharmacognostic tests. Stem (EEC) and leaf (EEF) extracts were obtained through maceration with ethanol, followed by phytochemical prospecting through thin layer chromatography. For in silico studies the terpenes were selected: (1S,2S,3R,4S)-1-methyl-4-(propan-2-yl)-cyclohexane-1,2,3,4-tetrol (A); 1,2,3,4-tetrahydroxy-p-methane (B); (1R,2S)-3-pmethen-1,2-diol (C); (1R,4S)-p-met-2-en-1-ol (D); 1,4-dihydroxyp-met-2-ene (E); 1-methyl-4β-isopropyl-1-cyclohexene-4α, 5α, 6α-triol (F); Ascaridol (G), where the programs Marvin JS, PreADMET, PASS online, Molinspiration Online were used, to evaluate the physical-chemical, pharmacokinetic, toxicological and activity prediction aspects. The powders were classified as coarse, with moisture content within the recommended parameters, saponins, neutral pH and low density being absent. In the phytochemical prospection, triterpenes and steroids, saponins and flavonic heterosides were detected. All compounds follow Lipinski’s rule; were well absorbed from the gastrointestinal tract; C, D, E and G are strongly bound to plasma proteins; C and D distributed widely in the central nervous system; D and E were not metabolized by CYP and all inhibited CYP; A and B were not mutagenic and F and G are carcinogenic. The plant drugs showed good quality, and the terpenes were present in these samples. In silico studies indicate that molecules C, F and G are promising for anti-inflammatory, antineoplastic and antiprotozoal activity.